Analisis Manajemen Rantai Pasok dengan Metode Supply Chain Operation Reference PT Fourmi Asha Sejahtera - Wistin Wistin; Firdaus Alamsjah (Jurnal Syntax Admiration, 2024)
In an era of economic development, business competition demands the acquisition of as many consumers as possible. This naturally requires a sound strategy in order to gain a competitive edge over rivals. The aim of this research is to evaluate the supply chain performance of Multi-level Marketing (MLM) companies by measuring SCM performance. SCM performance measurement is carried out using the SCOR model with the weights for each level divided equally and processing the actual data for each performance metric. After processing the data there are 7 SCOR performance metrics. Based on the results of data processing, the actual values are then normalized using the De Boer Snorm to obtain SCOR performance metric measurement values. The results obtained were a total score of 72.2 which is included in the good category, these results indicate that there is still a need to evaluate and improve performance